The Use of Modern Innovative Technologies in Foreign Language Teaching and its Effectiveness (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article provides information on modern methods of teaching foreign languages. There are also ideas about the use of modern innovative technologies in foreign language teaching and its effectiveness.